THE EFFECT OF ECONOMIC GROWTH AND CAPITAL EXPENDITURE TO HUMAN DEVELOPMENT INDEX (HDI) IN INDRAGIRI HULU DISTRICT - Heriasman Heriasman (JURNAL MANAJEMEN DAN BISNIS, 2020)
The purpose of this study is: To analyze the effect of economic growth and capital expenditure simultaneously on the Human Development Index (HDI) in Indragiri Hulu Regency. To analyze the effect of partial economic growth on the Human Development Index (HDI) in Indragiri Hulu Regency. To analyze the effect of capital expenditure partially on the Human Development Index (HDI) in Indragiri Hulu Regency. This research was conducted at the Regency of Idragiri Hulu, which lasted approximately six months. The data obtained were analyzed denagn using multiple linear regression, to test the effect between research variables. From the results of the study found that if the variable Economic Growth (X1) and Capital Expenditure (X2) the value is 0, then the Human Development Index (Y). if Economic Growth (X1) rises by one percent and capital expenditure (X2) remains the Human Development Index (Y) decreases. if capital expenditure (X2) increases by one percent and Economic Growth (X1) remains the Human Development Index (Y) decreases. The relationship between the variable Economic Growth and Capital Expenditure on the Human Development Index (HDI) there is a strong and positive relationship. The Human Development Index (HDI) of Indragiri Hulu Regency is influenced by Economic Growth and Capital Expenditures. F test results show that simultaneous economic growth and capital expenditure do not significantly influence the human development index (HDI) of Indragiri Hulu Regency. And the partial hypothesis T test. Economic growth has a negative and not significant effect on the human development index in Indragiri Hulu Regency. Partial capital expenditure has no significant effect on the human development index of Indragiri Hulu Regency.